The financing law and its impact on a territorial tax: ICA (2019)
The issuance of the Tax Reform Law 1943 of 2018 called the financing law brings the new economic recovery strategy with the unified tax under the simple simple taxation regime with elements such as the consolidation of the income tax, the Industry and Commerce Tax and its Complementary, notices and boards and the consumption tax.